EFEKTIFITAS LEMBAR KEGIATAN SISWA BERBASIS PENDEKATAN PROBLEM BASED LEARNING PADA MATERI PERBANDINGAN UNTUK SISWA SMP - Koentri Jayanti; Euis Eti Rohaeti; Ratna Sariningsih (Departement of Mathematics Education, 2019)
One of the learning efforts that are discovering the concept with the creation of the student activity sheet based approach to Problem Based Learning. The purpose of this research is to analyze the feasibility of Student Activity Sheets that have been made before actually used when the learning process. This descriptive qualitative research methods, with a sample of 33 students one of 228 West Bandung Regency. The instrument to be prepared is student activity sheet based approaches Problem Based Learning, the now expert validation material, linguist, connoisseur media, and now student response. As for the results of the research that is now 75% material expert validation, linguists 75%, 83%, and media expert question form student response 76%. It can be concluded that the students already there is an interest in working on is student activity sheet but should still be in the lead. Student activity sheet based approach to Problem Based Learning can be used in learning.